New records of parasitoid braconids (Hymenoptera: Braconidae) parasitoids of the fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) in Durango, Mexico - González-Maldonado, María Berenice; Coronado-Blanco, Juana María; Lomeli-Flores, J. Refugio (Revista Colombiana de Entomología, 2020)
In this paper, are listed some Species of the family Braconidae (Hymenoptera: Ichneumonoidea) present in corn crops in the State of Durango, Mexico. The presence of Meteorus arizonensis and Meteorus laphygmae (Euphorinae) is highlighted as new records of parasitoids of the fall armyworm, Spodoptera frugiperda. These new records contribute to the knowledge of the diversity of hymenopteran, which can also be used in biological control programs.